Immanent person of the holy spirit from anslem to lombard : divine communion in the spirit. - Knell, Matthew. (Paternoster, 2009)
This study shows that there has not yet been any comprehensive study of the person of the Holy Spirit in the twelth century, and that such a study has something to add to concepts of twelth-century thought as well as modern debates in pneumatology. The richness of debate that took place with the advent of scholasticism, and its clashes with more traditional approaches to Christian study, raised issues about western conception of the Spirit that were both grounded in Scripture and the church fathers' writings, and thoroughly tested by reason and debate.